Modern Analytical Chemistry - Harvey, David (McGraw-Hill, 2000)
Modern Analytical Chemistry is a one-semester introductory text that meets the needs of all instructors. With coverage in both traditional topics and modern-day topics, instructors will have the flexibilty to customize their course into what they feel is necessary for their students to comprehend the concepts of analytical chemistry